Opening of an icosahedral boron framework: A combined infrared spectroscopic and computational study - Fagiani, Matias R.; Zeonjuk, L. Liu; Esser, Tim K.; Gabel, Detlef; Heine, Thomas; Asmis, Knut R.; Warneke, Jonas (Chemical Physics Letters, 2015)
The opening of an icosahderal boron cage in the periodinated closo-dodecaborate B12I122- upon deiodination is studied using cryogenic ion trap vibrational spectroscopy combined with electronic structure calculations. Comparison of simulated vibrational spectra to the infrared photodissociation spectra of messenger-tagged B12I122- and B12In- (n = 7-9) formed by skimmer collision induced dissociation shows that the larger clusters absorb exclusively below 975 cm-1 and hence exhibit quasi-icosahedral B12-cage structures, while the higher energy absorptions in-between 1000 and 1300 cm-1 observed for n = 7 can only be recovered by considering a breakup of the icosahedral cage upon deiodination from n = 8 to n = 7.
CRIS-Team Scopus Importer:2023-03-20